Understanding the purpose of treatment and expectations in patients with inoperable lung cancer treated with palliative chemotherapy - Nowicki, Andrzej; Woźniak, Karolina; Krajnik, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : Informing cancer patients about various types of treatment and their adverse effects and communicating negative information is an important element of diagnostic and therapeutic procedures. Understanding the purpose of treatment and expectations, and socio-demographic factors in patients undergoing palliative chemotherapy because of lung cancer. Material and methods : The study included 100 patients with lung cancer at the age of 40–80 years (mean 63.1) in the Oncology Center in Bydgoszcz in 2013–2014. The diagnostic survey method with the author’s questionnaire was used. Results : Forty-one percent of patients were convinced that the purpose of chemotherapy is to cure the disease. Both inhabitants of small towns (population below 50 thousand) and large villages (p = 0.09) were similarly convinced about the effectiveness of chemotherapy. Seventy-three percent of inhabitants of small towns and 79% of country dwellers (p = 0.005) thought that chemotherapy is aimed at improving the quality of life. Patients with very good economic conditions responded that chemotherapy is designed to improve the quality of life more often than those with good and bad economic conditions, 90%, 88% and 60%, respectively (p = 0.001). With the increase in population the number of people who claimed that palliative chemotherapy prolongs their life increased, 71%, 77% and 90%, respectively (p = 0.03). Conclusions : The knowledge of patients with lung cancer about palliative chemotherapy is insufficient. Almost half of them do not understand the purpose of treatment and hope that chemotherapy will cure them of the disease. Most patients know that the aim of chemotherapy is to alleviate symptoms and improve quality of life and prolong their life. Half of the patients want to obtain information on treatment and half of them about life expectancy. Almost half of the patients feel stress and anxiety towards chemotherapy. Most patients do not use the help of a psychologist and do not feel such a need.